Proteolysis of CD44 at the cell surface controls a downstream protease network - Wöhner, Birte; Li, Wenjia; Hey, Sven; Drobny, Alice; Werny, Ludwig; Becker-Pauly, Christoph; Lucius, Ralph; Zunke, Friederike; Linder, Stefan; Arnold, Philipp (Frontiers in Molecular Biosciences, 2023)
The cell surface receptor cluster of differentiation 44 (CD44) is the main hyaluronan receptor of the human body. At the cell surface, it can be proteolytically processed by different proteases and was shown to interact with different matrix metalloproteinases. Upon proteolytic processing of CD44 and generation of a C-terminal fragment (CTF), an intracellular domain (ICD) is released after intramembranous cleavage by the γ-secretase complex. This intracellular domain then translocates to the nucleus and induces transcriptional activation of target genes. In the past CD44 was identified as a risk gene for different tumor entities and a switch in CD44 isoform expression towards isoform CD44s associates with epithelial to mesenchymal transition (EMT) and cancer cell invasion. Here, we introduce meprin β as a new sheddase of CD44 and use a CRISPR/Cas9 approach to deplete CD44 and its sheddases ADAM10 and MMP14 in HeLa cells. We here identify a regulatory loop at the transcriptional level between ADAM10, CD44, MMP14 and MMP2. We show that this interplay is not only present in our cell model, but also across different human tissues as deduced from GTEx (Gene Tissue Expression) data. Furthermore, we identify a close relation between CD44 and MMP14 that is also reflected in functional assays for cell proliferation, spheroid formation, migration and adhesion.